QUANTITATIVE DETERMINATION OF WATER SPECIATION IN ALUMINOSILICATE GLASS: A COMPARATIVE NMR AND IR SPECTROSCOPIC STUDY - Schmidt B.C.; Riemer T.; Dupree R.; Behrens H.; Kappes R. (My University, 2001)
Water speciation in hydrous aluminosilicate glasses (with NaAlSi3O8, KAlSi3O8, LiAlSi3O8 and LiAlSi4O10 compositions) was studied with infrared (IR) and static ¹H nuclear magnetic resonance (NMR) spectroscopy. Using IR spectroscopy, the water speciation was determined from the peak intensities (linear absorbance as well as integrated intensity) of the near-infrared (NIR) absorption bands at 4500 and 5200 cm⁻¹ assigned to structurally bonded hydroxyl groups and molecular H2O, respectively. For LiAlSi4O10 glasses, a new calibration of the linear and integral molar absorption coefficients of the IR absorption bands at 4500 and 5200 cm⁻¹ is presented. Using NMR spectroscopy, the water speciation was determined from the static ¹H NMR spectra acquired at temperatures between 170 and 130 K, where the ¹H NMR signal consists of a well-defined Pake doublet due to rigid water molecules and an overlapping, but narrower, central peak due to structurally bonded OH groups. The distinct nature of these two signals (doublet and Gaussian) enables a reliable deconvolution of the ¹H NMR spectra and quantitative determination of water speciation in the glasses. For a series of hydrous NaAlSi3O8 glasses containing 1.5–10 wt.% water, we found a very good agreement of water speciation determined by NMR and IR spectroscopy (about 4% standard deviation in OH concentration), demonstrating the reliability of both methods. Total water contents determined with ¹H NMR spectroscopy are in excellent agreement with results from Karl–Fischer titration (KFT, <2% standard deviation).